QADIMGI BAQTRIYA DAVLATI TARIXINING MUSTAQILLIK YILLARIDA TADQIQ ETILISHI TARIXSHUNOSLIGI - Bo'ronova Zarnigor, Saidova Muharram (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article is about the ancient state of Bactria. In the Bronze Age, a state system emerged in Bactria. Large architectural structures, such as palaces and temples, dating back to this period, have been discovered, and traces of high construction, crafts, and agricultural culture have been identified. By the 9th-8th centuries BC, a political entity of military significance was established in Bactria. This article provides information about the formation, development, and role of the ancient Bactrian state in Central Asia